Prevalence of congenital microcephaly and its risk factors in an area at risk of Zika outbreaks - Songying Shen; Wanqing Xiao; Lifang Zhang; Jinhua Lu; Anna Funk; Jianrong He; Si Tu; Jia Yu; Li Yang; Arnaud Fontanet; Wei Bao; Kar Keung Cheng; et al. (BMC, 2021)
Abstract Background Prevalence of neonatal microcephaly in populations without Zika-epidemics is sparse. The study aimed to report baseline prevalence of congenital microcephaly and its relationship with prenatal factors in an area at risk of Zika outbreak. Methods This study included singletons born after 24 gestational weeks in 2017-2018 at four hospitals in Guangzhou, China. Microcephaly was defined as a head circumference at birth >3SD below the mean for sex and gestational age. Prevalence of microcephaly was estimated by binomial exact method. Multivariable logistic regression was used to examine the associations of microcephaly with prenatal factors. The population attributable fraction (PAF) for associated risk factors was calculated. Results Of 46,610 live births included, 154 (3.3, 95% CI 2.8-3.9 per 1000 live births) microcephalies were identified. Maternal hepatitis B virus carriers (HBV, OR 1.80, 95% CI 1.05-3.10) and primipara (OR 2.68, 95% CI 1.89-3.81) had higher risk of having a microcephalic baby. Higher prevalence of microcephaly was observed in women who had premature labor (OR 1.98, 95% CI 1.17-3.34) and had a baby with fetal growth restriction (OR 16.38, 95% CI 11.81-22.71). Four identified factors (HBV, primiparity, preterm labor, and fetal growth restriction) contributed to 66.4% of the risk of microcephaly. Conclusions The prevalence of microcephaly in Guangzhou was higher than expected. This study identified four prenatal risk factors that, together, contributed to two-thirds of the increased risk of microcephaly. This is the first reported association between maternal HBV carrier status and microcephaly.